A study of the clinical profile of atrial fibrillation in a tertiary care super-specialty referral centre in Central Nepal - Gautam, MP; Gautam, S; Prasad, S Guru; Subramanyam, G; Ghimire, U (Journal of College of Medical Sciences-Nepal, 2013)
Background The conventional causes and risk factors for atrial fibrillation (AF) are somewhat arbitrary; overlap exists, multiple aetiologies are often present in one individual, and clinical presentation is non- specific. This study was an attempt to study the clinical and echocardiographic profile of patients with AF in a tertiary care super-specialty hospital of a developing country. Materials and Methods This study was conducted in College of Medical Sciences, Chitwan, Nepal throughout the year 2010. Subjects with AF, diagnosed based on clinical history, medical records and surface ECG, were included in the study. The presentation, types and causes of AF and structural as well as functional abnormalities were assessed. Results A total of 136 consecutive subjects were included in the study. The mean age was 42.40 (20.48) years ranging from 17 to 80 years. Majority of the AF subjects were female (54.41%). Among symptomatic cases, palpitation was the most common (23.53%) presentation followed by dyspnea (17.65%) and stroke or transient ischemic attack (15.44%). Asymptomatic presentation was also not uncommon (25%). Persistent AF was the most common form (31.62%). Rheumatic heart disease was the most common cause (33.09%) followed by lone atrial fibrillation (23.52%), coronary artery disease (16.18%), hypertension (8.82%) and thyrotoxicosis (7.35%). Other causes included chronic obstructive airway disease (5.88%), diabetes (2.94%), cardiomyopathy (1.47%), constrictive pericarditis (1.47%), myocarditis (0.74%) and infective endocarditis (0.74%). Nearly 65 % subjects had either structural or functional abnormalities in echocardiographic study; dilated left atrium was the most prevalent abnormality. Conclusion In contrast to the studies reported from developed nations, our subjects with AF were younger and female, the most common cause was RHD and the majority had either structural or functional abnormalities in echocardiographic study. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 9-16 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8679